ARQUITETURA E EDUCAÇÃO: Temáticas e sentidos do tratamento do espaço escolar na produção científica nacional na área da educação (2009-2021) - Vicente Carlos Ziliani (2022)
Much of the educational process that we undergo during our lives takes place inside the school. The school is constituted, among other things, by the school building and the school spaces, which also educate, as demonstrated in several researches. The physical school space (architecture of these buildings) has been the object of research in education, which shows how architecture is a relevant aspect in the schooling process and in the constitution of subjectivities. Architecture can be the translation of the movements that will be part of the context that will be constituted there, and also of the spaces built for education. The importance of thinking about the school space is justified, considering it as an issue that influences teaching, learning, and the quality of learning. In Brazil there is ample legislation to guide school buildings, showing concern for their quality. This study intends, on one hand, to contribute in the area of education with reflections on the importance of school spaces as an integral element of the educational processes and to demonstrate the importance of the perspective of including architecture and urbanism in the construction and adequacy of schools and spaces for teaching. The general objective is to determine the themes and meanings of how the school space appears in national scientific productions, in the period from 2009 to 2021. The methodology used was qualitative and is characterized as a bibliographic research or "state of knowledge", in addition to providing an opportunity for multidisciplinarity in discussions and debates on education and architecture, therefore, using the abstracts, the most significant works on the subject were selected, choosing a total of five studies for analysis, one from each region of Brazil and all focused on spaces in early childhood education. The research made it evident that every space that surrounds us affects and influences our learning. The school as a whole is essential for a quality education. The analysis of the selected researches identified the existence of different themes: educational policies in the school space; architecture applied in school spaces; organization of the school space; use of the space in education and senses - bureaucratic, functional, management and educational approach. These themes showed themselves, in the presented realities, in an interconnected way working together to set up an educational structure that effectively seeks a quality education and consequently a better society, including the variable of school spaces. Obviously, a school is based on a set of models, shaped by its several variables: project, management, resources, and, fundamentally, people. This work has made clear the unequivocal relationship of school spaces with education and its quality. Whenever treated as an educational element, the school environment has brought positive results in the education offered.The school architecture, thought as an educational element, brings quality to children's education, enabling diverse experiences, access to the most diverse materials available at school, accessibility to all, regardless of their physical or mental conditions, environmental comfort (lighting, ventilation, sound), enables interaction with peers, as well as with all components of school spaces (teachers, technicians, employees and children of all ages), however, respecting the regionalities, since the community is part of the educational context in which the child is.